Awake fiberoptic versus awake videolaryngoscopy in difficult intubation - Saud Erwi (Al-Azhar University, Faculty of Medicine (Damietta), 2019)
Background: Difficult intubation is usually encountered in daily work of anesthesia and intensive care. Different inventions and techniques were tried to deal with difficult intubation. Aim of the work:  To investigate the difference between awake fiberoptic and awake videolaryngoscopy in difficult intubation Methods: A two-years, randomized comparative study was conducted and included patients with ASA classes I to III, who were scheduled for elective surgical procedures with anticipated difficult intubation. Patient randomly allocated to fiberoptic intubation (FI) and videolaryngoscopy (VL) intubation. The outcome measures were time to tracheal intubation, intubation success, number of attempts and operator evaluation of the procedure. Results: Both groups were comparable as regard to patient demographics, ASA classifications, number of attempts and number of patients who experienced desaturation. The time to intubate was significantly shorter in VL when compared to FI group. The sedation score and ease scores were significantly lower in VL when compared to FI groups. Conclusions: Videolaryngoscopy-guided intubation in difficult cases was associated with better outcome than fiberoptic intubation. However, no failure was reported in both groups